The development of PSMZA ICT maintenance system - Mahmood, Raja Intan Sariah Raja (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2024)
The PSMZA ICT Maintenance System of was developed with the aim of helping to solve the management and operational issues faced by the ICT unit at Politeknik Sultan Mizan Zainal Abidin (PSMZA) . This system was developed to assist in efficiently and periodically managing ICT maintenance. The objective of developing this system is to replace the manual system with an online system and to aid the ICT management and PSMZA staff in making maintenance complaints faster and more effectively. By developing this system, all maintenance data and information can be recorded and updated properly. The waterfall model was used as a guide for system development, which included planning, analysis, design, implementation, and maintenance phases. This web-based system, involved three main scopes: Users (lecturers and administration staff) and Staff (technical support and administrators). The development of this system utilized a web-based platform technology. Software and programming languages used for the development of this system are HTML, CSS, JavaScript, bootstrap, PHP, and MYSQL. In conclusion, this system assists PSMZA staff in making direct, fast, and easy ICT maintenance complaints.